The impact of parenting style on malevolent creativity based on Chinese university students: a latent profile analysis - Cui, Xingnan; Zhang, Xiang; Zhang, Hua (Frontiers in Psychology, 2024)
Introduction This study investigated the association between parenting styles and malevolent creativity. Methods It used latent profile analysis to compare the differences in malevolent creativity between different combinations of parenting styles with an online sample (N = 620). Results The results of the study suggest that a three-profile solution best fits the data, and the three profiles were labelled positive open parenting, undifferentiated parenting and negative limited parenting. Subsequent analyses revealed that there were significant differences in malevolent creativity performance among the three parenting styles, with participants in the positive open parenting having more malevolent creativity. Those with undifferentiated parenting had the lowest scores. Discussion The findings provide theoretical guidance for parenting strategies. Future intervention studies on malevolent creativity should also consider the potential impact of parenting style to obtain better results.